Financial Integration in Asia Estimating the Risk-Sharing Gains for Australia and Other Nations - Mercereau, Benoît (International Monetary Fund, 2006)
Holding foreign assets reduces the volatility of a country''s income by allowing countries to share risk. Yet, financial integration is limited in Asia. This paper estimates how much Australia and other countries in the Asia-Pacific region would gain from greater financial integration. The results suggest that these welfare gains are large, which argues in favor of a progressive capital account liberalization across the region